1997
DOI: 10.2118/36680-pa
|View full text |Cite
|
Sign up to set email alerts
|

Salinity, Temperature, Oil Composition, and Oil Recovery by Waterflooding

Abstract: The effect of aging and displacement temperatures and brine and oil composition on wettability and the recovery of crude oil by spontaneous imbibition and waterflooding has been investigated. This study is based on displacement tests in Berea sandstone with three crude oils and three reservoir brines (RB's). Salinity was varied by changing the concentration of total dissolved solids (TDS's) of the synthetic brine in proportion. Salinity of the connate and invading brines can have a major influence on wettabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
299
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(321 citation statements)
references
References 8 publications
19
299
1
2
Order By: Relevance
“…The highest recovery was achieved by initially saturating the core with calcium brine, injecting Na brine until residual oil saturation was achieved, then injecting calcium brine. Tang and Morrow (1997) investigated the effects of connate and injection brine salinity, aging time and temperature on water flooding and imbibition with 3 different crude oils and 3 different brines. They concluded that in water floods with constant connate brine salinity and variable injected brine salinity, diluting injected brine 100 times produced *5 % incremental oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The highest recovery was achieved by initially saturating the core with calcium brine, injecting Na brine until residual oil saturation was achieved, then injecting calcium brine. Tang and Morrow (1997) investigated the effects of connate and injection brine salinity, aging time and temperature on water flooding and imbibition with 3 different crude oils and 3 different brines. They concluded that in water floods with constant connate brine salinity and variable injected brine salinity, diluting injected brine 100 times produced *5 % incremental oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Wettability of the reservoir rock is a key factor in thermal displacement efficiency (Hoffman and Kovscek 2004). Some crude oil/brine/rock systems are noted to shift toward water wetness as a result of heating (Tang and Morrow, 1997;Tang and Kovscek, 2004). The mechanisms of wettability alteration at high temperature, however, remain in question.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show a decrease in residual oil saturation by water injection with an increase in temperature systematically for both consolidated and unconsolidated systems (Edmondson, 1965, Poston, et al, 1970, Maini and Batycky, 1985. Tang and Morrow (1997) demonstrated for Berea sandstone that an increase in temperature always resulted in increased water-wetness and increased oil recovery by either spontaneous water imbibition or waterflooding. Similar behavior was also observed for North Sea carbonate rocks (Dangerfield and Brown, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In recent twenty years, the successful practices of brine-modified flooding, including low salinity waterflooding (LSF) in sandstone [1][2][3][4][5][6] and seawater or modified seawater flooding in carbonate, 1,[7][8][9][10][11][12] have proved that ionic composition of the injected brine can significantly influence waterflooding efficiency. These new waterflooding strategies are economical and environment-friendly, and thus have attracted increasing interests from oil industry.…”
Section: Introductionmentioning
confidence: 99%